Effect of FeCl2 concentration on the properties of magnetic nanoparticles by using Massart's procedure - Ang, Beechin; Yaacob, Iskandar Idris; Chew, C. S. (Penerbit Universiti Kebangsaan Malaysia, 2014)
The effect of variation of FeCl2 concentration on the properties of magnetic nanoparticles produced by Massart's procedure was investigated. Samples with different FeCl2 concentration of 0.1, 0.8, 1.0, 1.2 and 1.5 M were produced. In this technique, an aqueous mixture of ferrous and ferric chloride was co-precipitated under controlled conditions to yield magnetic iron oxide nanoparticles. Thermogravimatric analysis (up to 700°C) showed a continuous weight loss from room temperature to 200°C that was mainly due to evaporation of water from the sample. Above 230°C, no more weight loss was observed indicating the stability of the maghemite nanoparticles. The lattice parameter of the samples obtained from X-ray diffraction analysis showed that the nanoparticles formed were maghemite (γ-Fe2O3). The crystallite sizes calculated from the broadening of XRD peaks were 6.79, 6.56, 6.15, 6.72 and 7.24 nm for FeCl2 concentration of 0.1, 0.8, 1.0, 1.2 and 1.5 M, respectively. The magnetization curves showed no hysteresis indicating that the particles were superparamagnetic. The least upper bound of the 'magnetic' sizes calculated were 7.53, 6.29, 5.92, 6.41 and 8.04 nm and the physical sizes measured from TEM images were 5.97, 6.02, 4.98, 5.35 and 5.98 nm, respectively. The crystallite, magnetic and physical sizes were similar, indicating that the particles are mon°Crystals.